PREVENTING SEXUAL VIOLENCE IN SCHOOL IN COSTA RICA: CROSS-CULTURAL ADAPTATION OF AN EDUCATIONAL BOOKLET - Rivera, Alejandra Isabel Vargas; Pinheiro, Patrícia Neyva da Costa; Mondragón-Sánchez, Edna Johana; Silva, Kellane Lima da; Vasconcelos, Fatima Karine Apolonio; Costa, Maria Isabelly Fernandes da (Cogitare Enfermagem, 2022)
Objective: to perform the translation and cross-cultural adaptation of the educational booklet "Prevention of sexual violence at school" for the reality of Costa Rica. Method: methodological study conducted with 61 adolescents between 10 and 13 years old; two Costa Rican translators, two Brazilian translators, one professional in Spanish linguistics, one professional in Brazilian linguistics and seven judges. The data collection period was carried out between the months of June to December 2017. Results: there were inconsistencies in the use of personal pronouns in Spanish ("vos", "tu", and "usted"), absence of "inclusive language", employment of language and words not used by the target population, and discrepancies in themes, images, and about the cultural reality of Costa Rica. The decision was "needs reform" in appearance and homogenization of pronouns. Conclusion: the booklet can be used in various environments for health education actions, in the case of this study, in schools. A fundamental part of nursing professionals is to be educators, providing tools to adolescents by means of scientifically evaluated materials and facilitating teaching and learning.